2008
DOI: 10.1203/pdr.0b013e31815b4842
|View full text |Cite
|
Sign up to set email alerts
|

Ventricle-Specific Metabolic Differences in the Newborn Piglet Myocardium In Vivo and During Arrested Global Ischemia

Abstract: Ventricular dysfunction is reported greater in the left (LV) versus right ventricle (RV) in infants following surgically induced ischemia. Ventricle-specific differences in baseline metabolism may alter response to ischemia thus affecting postischemic functional recovery. This study identifies ventricle-specific metabolic differences in the newborn (piglet) heart at baseline (working) and during ischemia (arrested). Baseline LV citrate synthase (CS) and hydroxyacyl-CoA dehydrogenase (HAD) activities were 15% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Although our study demonstrates similarities between adults and newborn rabbits for SOD, most published studies show important species-dependent changes. In pigs, for example, SOD and catalase increase during the first few weeks of life before stabilizing [32], whereas rats generally demonstrate an age-dependent decrease in antioxidant levels [35]. In addition, we found that in newborns, the right ventricle had significantly decreased SOD activity compared with the left ventricle.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although our study demonstrates similarities between adults and newborn rabbits for SOD, most published studies show important species-dependent changes. In pigs, for example, SOD and catalase increase during the first few weeks of life before stabilizing [32], whereas rats generally demonstrate an age-dependent decrease in antioxidant levels [35]. In addition, we found that in newborns, the right ventricle had significantly decreased SOD activity compared with the left ventricle.…”
Section: Discussionmentioning
confidence: 93%
“…For example, previous studies demonstrated that during IR injury in newborn pigs, the left ventricle had significantly less ATP than the right ventricle as well as increased hydrogen ion formation [32, 48]. Although there were no data to determine whether this was the cause of diminished function, it does outline that the right and left ventricles experience different responses to the same injury.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in neonatal animal models have suggested that enhanced myocardial reliance on carbohydrate metabolism plays an important role in determining postischemic dysfunction (3,29). The neonatal heart demonstrates a shift in substrate metabolism from predominantly carbohydrate to fatty acid oxidation within the first 1-2 wk after birth (2,4,18).…”
mentioning
confidence: 99%
“…Interestingly, this study demonstrated that despite greater and more rapid accumulation of anaerobic end-products, the newborn female myocardium had a greater ability to undergo glycogenolysis dur-ing ischemia suggesting the presence of sex-specific differences in glycolytic enzyme sensitivity to anaerobic endproducts in the newborn myocardium. In addition, previous work demonstrated that in newborns, the left ventricle despite having higher glycogen levels than the right ventricle had greater anaerobic end-product accumulation and lower energy levels during ischemia (25). The current work suggests this ischemic profile is exacerbated in females, putting them at even greater risk.…”
Section: Discussionmentioning
confidence: 49%
“…Previous work demonstrated that in newborns, compared with the right ventricle, the left ventricle had enhanced glycolytic capacity which resulted in greater anaerobic endproduct accumulation and lower energy levels during ischemia (25). This study is the first to investigate and characterize sex-specific differences in baseline and ischemic metabolism in this high-risk ventricle of the newborn.…”
Section: Discussionmentioning
confidence: 76%